PERAN KERJASAMA TIM DALAM MEMEDIASI PENGARUH MOTIVASI DAN KOMUNIKASI TERHADAP KINERJA KARYAWAN PADA HOTEL ANEKA RESTORAN & SPA - Mahandika, Mochammad Bayu; Sudarnaya, Ketut (Jurnal Daya Saing, 2023)
Human resources have a very important role to achieve the goals of anorganization or company, for that we need resources that can work together inteams. It takes such high motivation and communication to build teamwork so thatemployee performance increases. The purpose of this study was to determine therole of teamwork in mediating the influence of motivation and communication onemployee performance at various hotels, restaurants & spas. The number ofemployees at the Aneka Lovina Hotel is 72 people who will be used in the samplein this study. This research was conducted using a quantitative approach. Thedata collection method used in this research is the method of distributingquestionnaires and data analysis techniques using the SmartPLS application.The results of this study state that the value of the parameter coefficient ofthe relationship between motivation and teamwork is 0.096 and the t-statisticvalue is 2.102, Communication towards teamwork is 0.742 and the t-statisticvalue is 13.077, motivation to employee performance is 0.716 and the t-value isstatistics of 12,571, communication on employee performance of 0.546 and tstatistic value of 5.231, motivation on employee performance through teamworkof 0.048 and t-statistic value of 0.027, communication on employee performancethrough teamwork of 0.372 and t-statistic value of 4,275. It can be stated that allconstructs have a positive and significant effect.